Oxytocin increases emotional theory of mind, but only for low socioeconomic status individuals. Issue 3 (March 2020) - Sun, Rui; Vuillier, Laura; Deakin, Julia; Kogan, Aleksandr
Abstract: Studies have linked oxytocin to emotional theory of mind (eToM) — the ability to recognise and understand others' emotions. However, multiple replications have so far failed to reach a consistent result. Growing evidence suggests that oxytocin's positive effects on social-emotional tasks such as eToM are highly dependent on trait-level individual differences. In the present study, we theorised that socioeconomic status (SES) could influence oxytocin's impact on emotional mentalising processes. We tested our hypothesis in a double-blind between–subjects oxytocin nasal spray study on 147 Caucasian white male participants in the United Kingdom. In accordance with our hypothesis, we found that oxytocin (as compared to placebo) did boost emotional theory of mind, but only in people from low subjective SES backgrounds. Our results expand existing theory on how individual differences moderate oxytocin's role on social behaviours. Abstract : Neuroscience; Psychology; Oxytocin; Emotional theory of mind (eToM); Socioeconomic Status (SES); Individual differences; Read the mind in the eyes test (RMET).